Detection of Resistance to Fluoroquinolones and Second-Line Injectable Drugs Among Mycobacterium tuberculosis by a Reverse Dot Blot Hybridization Assay - Li G; Guo Q; Liu H; Wan L; Jiang Y; Li M; Zhao LL; Zhao X; Liu Z; Wan K (Infection and Drug Resistance, 2020)
Guilian Li,1,* Qian Guo,1,2,* Haican Liu,1 Li Wan,1 Yi Jiang,1 Machao Li,1 Li-li Zhao,1 Xiuqin Zhao,1 Zhiguang Liu,1 Kanglin Wan1 1State Key Laboratory for Infectious Disease Prevention and Control, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, National Institute for Communicable Disease Control and Prevention, Chinese Center for Disease Control and Prevention, Beijing 102206, People’s Republic of China; 2Department of Molecular Biology, Shanghai Jiao Tong University Affiliated Sixth People’s Hospital, Shanghai 200233, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kanglin Wan Email wankanglin@icdc.cnBackground: Reliable and timely determination of second-line drug resistance is essential for early initiation effective anti-tubercular treatment among multi-drug resistant (MDR) patients and blocking the spread of MDR and extensively drug-resistant tuberculosis. Molecular methods have the potency to provide accurate and rapid drug susceptibility results. We aimed to establish and evaluate the accuracy of a reverse dot blot hybridization (RDBH) assay to simultaneously detect the resistance of fluoroquinolones (FQs), kanamycin (KN), amikacin (AMK), capreomycin (CPM) and second-line injectable drugs (SLIDs) in Mycobacterium tuberculosis.Methods: We established and evaluated the accuracy of the RDBH assay by comparing to the phenotypic drug susceptibility testing (DST) and sequencing in 170 M. tuberculosis, of which 94 and 27 were respectively resistant to ofloxacin (OFX) and SLIDs.Results: The results show that, compared to phenotypic DST, the sensitivity and specificity of the RDBH assay for resistance detection were 63.8% and 100.0% for OFX, 60.0% and 100.0% for KN, 61.5% and 98.1% for AMK, 50.0% and 99.3% for CPM, and 55.6% and 100% for SLIDs, respectively; compared to sequencing, the sensitivity and specificity of the RDBH assay were 95.2% and 100.0% for OFX, 93.8% and 100.0% for SLIDs or KN (both based on mutations in rrs 1400 region and eis promoter), and 91.6% and 100.0% for AMK or CPM (both based on mutations in rrs 1400 region), respectively. The turnaround time of the RDBH assay was 7 h for testing 42 samples.Conclusion: Our data suggested that compared to sequencing, the RDBH assay could serve as a rapid and reliable method for testing the resistance of M. tuberculosis against OFX and SLIDs, enabling early administration of appropriate treatment regimens among MDR tuberculosis patients.Keywords: Mycobacterium tuberculosis, drug resistance, reverse dot blot hybridization, fluoroquinolones, second-line injectable drugs, ofloxacin, kanamycin, amikacin, capreomycin